PENGARUH BRAND AWARENESS DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK FREEKICK SECOND DI KARAWANG - Pelangi, Dina Reira; Nurlenawati, Netti; Triadinda, Dexi (Universitas Respati Indonesia, 2025)
This study examines the influence of brand awareness and brand image on purchasing Karawang Freekick Second products. Questionnaires were sent to 120 Freekick Second customers for quantitative studies. Sampling was done by purposive sampling if the respondents had purchased the product. Validity and reliability tests were conducted on 30 respondents before data collection. Brand awareness, brand image, and purchasing choices were measured using a Likert scale. While a good brand image gives customers a sense of quality and exclusivity. This second variable has a significant role in purchasing decisions, with a coefficient of determination of 37.1%. Data were analyzed using SPSS software version 24. The implications of this study explain the need for Freekick Second to implement a marketing strategy that focuses more on increasing brand awareness and product quality, as well as effective communication in building consumer trust and loyalty. It is expected that this study will add insight into the development of marketing strategies in the thrifting fashion industry. Keywords: Brand Awareness, Brand Image, Purchasing Decisions, Freekick Second, Thrifting Fashion